Wissenschaftliches Fehlverhalten – ein Problem in der deutschen Volkswirtschaftslehre? - Necker, Sarah (Perspektiven der Wirtschaftspolitik, 2012)
Systematic evidence on scientific misbehavior in economics is limited; so far no study explicitly deals with the attitudes and behavior of German economists. In this paper, results of a survey among the members of the Vereins für Socialpolitik conducted in autumn 2010 are reported. According to the results, serious misbehavior like the fabrication of data or pure plagiarism is rare. German economists reject such behavior unanimously, only a handful of respondents admit it. A problem rather consists in the low reporting of observed misbehavior. Some forms of questionable research practices are also of concern. For example, strategic behavior in the publication process is wide-spread, although the majority of the German economists find it unacceptable. © 2012 die Autoren Perspektiven der Wirtschaftspolitik © 2012 Verein für Socialpolitik.
CRIS-Team Scopus Importer:2022-05-03